Role of vertebral corner inflammation and fat deposition on MRI on syndesmophyte development detected on whole spine low-dose CT scan in radiographic axial spondyloarthritis - Stal, Rosalinde (2022)
Publisher Copyright: © Author(s) (or their employer(s)) 2022. Re-use permitted under CC BY. Published by BMJ.